2001
DOI: 10.1088/0957-0233/12/7/306
|View full text |Cite
|
Sign up to set email alerts
|

Spectral modelling of curved long-period fibre gratings

Abstract: Curved long-period fibre gratings are described in terms of a new model, based on a matrix method. The variations in the formulation of the main equations, which define the spectral behaviour of a long period fibre grating, are presented. Good agreement between experimental data that had previously been reported and results from the proposed model are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Dip 1 is the original transmission dip and dip 2 is the new dip. [18] In the literature the splitting has in several papers [69][70][71] been explained by stating that the fibre-curvature breaks the degeneracy of the cladding modes that are normally coupled to in the straight fibre. These non-degenerate modes, with power concentrated on opposite sides of the fibre core, then propagate with different speeds due to the difference in longitudinal strain above and below the fibre axis.…”
Section: Bend Sensorsmentioning
confidence: 99%
“…Dip 1 is the original transmission dip and dip 2 is the new dip. [18] In the literature the splitting has in several papers [69][70][71] been explained by stating that the fibre-curvature breaks the degeneracy of the cladding modes that are normally coupled to in the straight fibre. These non-degenerate modes, with power concentrated on opposite sides of the fibre core, then propagate with different speeds due to the difference in longitudinal strain above and below the fibre axis.…”
Section: Bend Sensorsmentioning
confidence: 99%
“…Several papers [61][62][63] have explained the splitting by stating that the fiber-curvature breaks the degeneracy of the cladding modes that are normally coupled to in the straight fiber. These nondegenerate modes, with power concentrated on opposite sides of the fiber core, then propagate with different speeds due to the difference in longitudinal strain above and below the fiber axis.…”
Section: Long-period Gratings As Bend Sensorsmentioning
confidence: 99%
“…The constant resonance wavelength, as the sensor is bent (figure 4.15), could be due to two reasons. First, it has been shown that the change in the effective refractive index modulation of the gratings in the fiber core is less than 0.1 % for huge curvature [18] and since the bending curvature in this experiment was not large enough to induce a major change in the effective refractive index modulation, the resonance wavelength of the ELPG spectrum would not be affected. In addition, with the external medium refractive index higher than that of cladding, the phase matching Chapter 4…”
Section: Response Of Elpg To Bendingmentioning
confidence: 80%
“…Study shows that bending of the LPG results in a red shift of LPG resonance wavelength. Theoretical analysis showed that the spectral shift of the resonance wavelength is due to the change in the period of the gratings and the strain caused in the core of the optical fiber [18]. Despite non-linear output response, the sensor yields a total wavelength shift of 16 nm for a bending curvature of 4.4m" 1 .…”
Section: The Advantages Of Lpgs Over Fbgs Include the Elimination Of mentioning
confidence: 99%
See 1 more Smart Citation